Effect of Sustainable Cities on the Urban Heat Island and Human Thermal Comfort-Dubai Sustainable City as A Case Study (Future Cities and Environment, 2025)
Due to the adverse effects that rising air temperatures have on urban dwellers' health and thermal comfort, the urban heat island phenomenon (UHI) is a global problem that worries architects. The high energy consumption of buildings, particularly in hot, arid areas, to maintain comfortable indoor temperature conditions for users, is one of the primary causes of UHI. Because of the rise in carbon dioxide levels, urban heat islands are becoming more common, especially in urban areas. Urban geometry is a key factor affecting the intensity of the UHI phenomena. As a result, the aim of this study is to evaluate and contrast the impact of sustainable cities and conventional urban forms on lowering outdoor air temperatures, reducing UHI effects, and improving human thermal comfort in the United Arab Emirates (UAE). Specifically, this research aims to assess how the urban form and layout of Dubai's Sustainable City compare with a conventional residential district in Ajman, focusing on their influence on microclimate and thermal comfort. The study uses a qualitative approach, employing ENVI-met urban microclimate simulation software to assess the UHI effects in both districts. The findings revealed that lower air temperatures were observed in the sustainable district, particularly between the hours of 10 a.m. and 6 p.m. On August 21, at 1 p.m., the sustainable district exhibited air temperatures 1.11 °C to 2.90 °C lower than those in the conventional district. The average air temperature at 1 p.m. was 40.52 °C, which was 2.02 °C cooler than in the conventional district. Additionally, the sustainable district showed lower levels of Predicted Mean Vote (PMV), indicating improved human thermal comfort. This discrepancy was attributed to the courtyards and semi-attached buildings in the sustainable district, which enhanced shading and reduced variables affecting sky views. This study aims to demonstrate the beneficial effects of passive design strategies associated with sustainable urban forms, such as compact layouts and courtyards, in lowering outdoor air temperatures and improving thermal comfort in hot, arid climates.